A large familial cluster and sporadic cases of frontal fibrosing alopecia in Brazil reinforce known human leucocyte antigen (HLA) associations and indicate new HLA susceptibility haplotypes - Ramos, P. M. [UNESP]; Garbers, L. E.F.M. [UNESP]; Silva, N. S.B. [UNESP]; Castro, C. F.B. [UNESP]; Andrade, H. S. [UNESP]; Souza, A. S. [UNESP]; Castelli, E. C. [UNESP]; Miot, H. A. [UNESP] (Wiley, 2020)
Background: Frontal fibrosing alopecia (FFA) is a lymphocytic scarring alopecia whose worldwide incidence is rising. Environmental triggers combined with genetic predisposition represent one of the current hypotheses in FFA aetiology. Familial clusters are opportunities to investigate the genetic basis of diseases. Objectives: Assess human leucocyte antigen (HLA) genetic variability in a Brazilian sample of a large familial cluster (six sisters and one daughter) with FFA, unnafected familiar members and sporadic cases of FFA. Methods: We addressed the HLA-A, HLA-B, HLA-C, HLA-G and HLA-E genetic variability in this family and in seven sporadic FFA cases, comparing allele frequencies with those reported for the São Paulo State from Brazil. Results: Two susceptibility haplotypes, C*17:01:01:02/B*42:01:01:01 and C*07:02:01:03/B*07:02:01:01, were identified among familial cases and also in sporadic cases. The first haplotype is rare among Brazilians, and it was not previously reported as being associated with FFA. Both alleles were found in some different unaffected familiars, what emphasizes the role of environmental triggers in disease development. HLA-A, HLA-G and HLA-E genes were not associated to familiar nor FFA sporadic cases. Conclusion: The identification of susceptibility haplotypes in FFA reinforces the genetic predisposition to the disease.